Modified Sick Neonatal Score: A Modified Score to Evaluate the Burden of Neonatal Morbidity in a Tertiary Care Hospital (Bangladesh Journal of Child Health, 2024)
Background: To assess neonatal mortality, many validated scores have been developed. The modified sick neonatal score (MSNS) is an easy, less complex suitable for both term and preterm neonates. This study was conducted to predict mortality upon admission to a NICU using the MSNS score.Methods: An observational study was conducted in the Department of Neonatology, BSMMU, Dhaka, over a period of one year. Parameters for MSNS score were collected from data sheet. Outcome expressed as survived or expired. All data were analyzed using SPSS 20. To determine the cutoff value for predicting mortality, a receiver operating curve was generated. The cutoff score’s sensitivity, specificity, positive predictive value, and negative predictive value were calculated.Results: Among the enrolled 114 neonates, mean gestational age and mean birth weight were 34.22±3.10 weeks and 1967.87±752.33g respectively. About 75.4% neonates were